PENGARUH DEBT TO EQUITY RATIO (DER), CURRENT RATIO (CR), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP EARNING PER SHARE (EPS) PADA PERUSAHAAN PROPERTY, REAL ESTATE, DAN KONTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - A.A. Istri Cynthia Bahari Dewi (Hita Akuntansi dan Keuangan, 2021)
Empirically anatomize the impact of Debt to Equity Ratio, Current Ratio, and Total Asset Turnover towards Earning Per Share at property, real estate, and construction companies that registered in Indonesian Stock Exchange (IDX) is the goal of this research. Purposive sampling method is used to determination of the number of samples. 35 companies of property, real estate, and construction companies chosen as sample on this research using some criteria throughout period 2016-2019. This research using multiple linear regression analysis to test the hypothesis. The findings of this research were: Debt to Equity Ratio had no significant effect on Earning Per Share, Current Ratio had no significant effect on Earning Per Share, and Total Asset Turnover had positive and significant effect on Earning Per Share.